2022
DOI: 10.3390/ijerph192416422
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Four-Week Online Mindfulness Training Course on Individual Mindfulness Skills and Personal Perception of Stress in Company Employees Working from Home

Abstract: Working from home comes with many benefits. However, employees are often exposed to various stressors when working outside of the traditional workplace environment. The subjective experience of these stressors is related to one’s perception of the situation and the perceived resources available. As working from home has become the new normal for many during the COVID-19 pandemic, it is in the interest of companies to provide employees with tools to cope with these stressors. One such tool is online mindfulness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Spijkerman et al [38] conducted a meta-analysis and found that online mindfulness training significantly improves mindfulness skills, reduces stress, and enhances well-being. Additionally, previous studies have shown that predetermined mindfulness skills can be improved in as little as four weeks through online training, resulting in positive effects on perceived stress levels [36]. The significance of these findings lies in their potential to improve accessibility and ensure practicality and adaptability.…”
Section: Intervention Formatmentioning
confidence: 89%
See 1 more Smart Citation
“…Spijkerman et al [38] conducted a meta-analysis and found that online mindfulness training significantly improves mindfulness skills, reduces stress, and enhances well-being. Additionally, previous studies have shown that predetermined mindfulness skills can be improved in as little as four weeks through online training, resulting in positive effects on perceived stress levels [36]. The significance of these findings lies in their potential to improve accessibility and ensure practicality and adaptability.…”
Section: Intervention Formatmentioning
confidence: 89%
“…Research has shown that predefined mindfulness skills can be improved in just four weeks of online training [36]. This training has a demonstrable positive impact on subjective stress perceptions.…”
Section: Hypothesesmentioning
confidence: 99%